PENERAPAN METODE RUMUS SAKTI PADA TSULATSY MUJARRAD DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN SHARAF PADA SISWI KELAS VIII MTS ABU HURAIRAH KOTA MAKASSAR - Tri Putriwati; Wahyudin; Agussalim Beddu Malla (STKIP Subang, 2026)
This study aims to determine the implementation of the Rumus Sakti method in improving students’ basic morphology (sharaf) skills in Tsulatsy Mujarrad, to identify the improvement of students’ learning outcomes, and to analyze the supporting and inhibiting factors in the learning process. This research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 11 eighth-grade students of MTs Abu Hurairah. The results showed that the implementation of the Rumus Sakti method significantly improved students’ learning outcomes. In the pre-cycle stage, only 2 students (18%) achieved mastery with an average score of 56.6. In cycle I, the number increased to 4 students (36.3%) with an average score of 76.3. In cycle II, the number of students achieving mastery increased significantly to 10 students (90%) with an average score of 88. The supporting factors included increased student enthusiasm, activeness, and self-confidence during the learning process. Meanwhile, the inhibiting factors included differences in students’ initial abilities and their tendency to memorize formulas without understanding the underlying concepts. Therefore, it can be concluded that the Rumus Sakti method is effective in improving students’ basic sharaf skills and Arabic learning outcomes.